Uncovering metabolism in rhabdomyosarcoma. Issue 2 (17th January 2016) - Monti, Eugenio; Fanzani, Alessandro
Abstract: Rhabdomyosarcoma (RMS) is a myogenic tumor classified as the most frequent soft tissue sarcoma affecting children and adolescents. The histopathological classification includes 5 different histotypes, with 2 most predominant referred as to embryonal and alveolar, the latter being characterized by adverse outcome. The current molecular classification identifies 2 major subsets, those harboring the fused Pax3-Foxo1 transcription factor generating from a recurrent specific translocation (fusion-positive RMS), and those lacking this signature but harboring mutations in the RAS/PI3K/AKT signaling axis (fusion-negative RMS). Since little attention has been devoted to RMS metabolism until now, in this review we summarize the "state of art" of metabolism and discuss how some of the molecular signatures found in this cancer, as observed in other more common tumors, can predict important metabolic challenges underlying continuous cell growth, oxidative stress resistance and metastasis, which could be the subject of future targeted therapies.